An improved analytical model for two-step corbels in a precast concrete system. (1st June 2023) - Neuberger, Ygor Moriel; Araújo, Daniel de Lima
Highlights: A 3D finite element model is developed for the two-step corbel. A database with 126 corbels is made by parametric analysis. An analytical model is proposed for the design of two-step corbels. The proposed analytical model has strength reduction factors calculated. Abstract: Corbels are a common element in the beam–column connections of precast concrete structures. This paper analyses the failure of a two-step corbels system using computational modeling. A finite element model is developed and calibrated using the test results for two-step corbels without secondary reinforcement but with steel fiber–reinforced concrete. A database is developed from the parametric analyses of two-step corbels, varying the a/d ratio (0.34–0.76), the rate of the main reinforcement (0.19–0.50%), the compressive strength of the concrete (30–70 MPa) and the amount of steel fibers (1.0% and 1.5%). An improved analytical model, using the developed database, is proposed to design the two-step corbels. The reliability of the proposed analytical model is evaluated using a second database, developed in this paper, and a strength reduction factor of 0.66 for failure by yielding of the main reinforcement and 0.56 for failure by crushing of the concrete strut, were obtained. Therefore, the improved analytical model obtained for the design of two-step corbels represents an advance, in terms of structural safety and economy, when compared to the previous analytical models recommended in the literature.